If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (y + -3) + -1(y + 4) = 2y Reorder the terms: (-3 + y) + -1(y + 4) = 2y Remove parenthesis around (-3 + y) -3 + y + -1(y + 4) = 2y Reorder the terms: -3 + y + -1(4 + y) = 2y -3 + y + (4 * -1 + y * -1) = 2y -3 + y + (-4 + -1y) = 2y Reorder the terms: -3 + -4 + y + -1y = 2y Combine like terms: -3 + -4 = -7 -7 + y + -1y = 2y Combine like terms: y + -1y = 0 -7 + 0 = 2y -7 = 2y Solving -7 = 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -7 + -2y = 2y + -2y Combine like terms: 2y + -2y = 0 -7 + -2y = 0 Add '7' to each side of the equation. -7 + 7 + -2y = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -2y = 0 + 7 -2y = 0 + 7 Combine like terms: 0 + 7 = 7 -2y = 7 Divide each side by '-2'. y = -3.5 Simplifying y = -3.5
| 3(a-3)=2(a+2) | | 3x+9=3x-27 | | 2(a-3)=2(a+4) | | 0.8-0.6+0.3=5 | | n*2+n-42=0 | | 6x^2-8x-333=0 | | 36x+6=36x+6 | | 3x-2x-6x=-8-2 | | x^2+3x-340=0 | | 25x+110-x=18.50 | | 25b^2-15=0 | | 82=14-6+d | | P(x)=2x^3-6x^2-26x+30 | | 5x^2-64=0 | | x^2+4x-117=0 | | 6m^2-30=0 | | r-12-8+7=27 | | x^2+2x-840=0 | | 2m+1+8m-3=36 | | 25+p=117 | | 4=f/8 | | 12x-108=0 | | 3x+5=8x-10 | | 5x-2y=25 | | -6x+2=3x | | 4(2a-3b)+a-7= | | 159x+75=15 | | x^2-7x-588=0 | | 2x^2+4x-177=0 | | -6y+6=-8y-4 | | g^2-11g-26= | | 2(u-1)+4u=3(u-1)+7 |